Systematic analytical characterization of new psychoactive substances: A case study - Lobo Vicente, Joana; Chassaigne, Hubert; Holland, Margaret V; Reniero, Fabiano; Kolář, Kamil; Tirendi, Salvatore; Vandecasteele, Ine; Vinckier, Inge; Guillou, Claude (Forensic science international, 2016)
New psychoactive substances (NPS) are synthesized compounds that are not usually covered by European and/or international laws. With a slight alteration in the chemical structure of existing illegal substances registered in the European Union (EU), these NPS circumvent existing controls and are thus referred to as "legal highs". They are becoming increasingly available and can easily be purchased through both the internet and other means (smart shops). Thus, it is essential that the identification of NPS keeps up with this rapidly evolving market. In this case study, the Belgian Customs authorities apprehended a parcel, originating from China, containing two samples, declared as being "white pigments". For routine identification, the Belgian Customs Laboratory first analysed both samples by gas-chromatography mass-spectrometry and Fourier-Transform Infrared spectroscopy. The information obtained by these techniques is essential and can give an indication of the chemical structure of an unknown substance but not the complete identification of its structure. To bridge this gap, scientific and technical support is ensured by the Joint Research Centre (JRC) to the European Commission Directorate General for Taxation and Customs Unions (DG TAXUD) and the Customs Laboratory European Network (CLEN) through an Administrative Arrangement for fast recognition of NPS and identification of unknown chemicals. The samples were sent to the JRC for a complete characterization using advanced techniques and chemoinformatic tools. The aim of this study was also to encourage the development of a science-based policy driven approach on NPS. These samples were fully characterized and identified as 5F-AMB and PX-3 using (1)H and (13)C nuclear magnetic resonance (NMR), high-resolution tandem mass-spectrometry (HR-MS/MS) and Raman spectroscopy. A chemoinformatic platform was used to manage, unify analytical data from multiple techniques and instruments, and combine it with chemical and structural information.
Keywords: Synthetic cannabinoids; Crime; Forensic Toxicology; Belgie; soudní toxikologie; lidé; Belgium; HR-MS/MS; NMR; hmotnostní spektrometrie; Psychotropic Drugs; magnetická rezonanční spektroskopie; Substance Abuse Detection; New psychoactive substances; psychotropní léky; Benzodiazepines; Mass Spectrometry; Magnetic Resonance Spectroscopy; odhalování abúzu drog; zločin; Humans